"If Lil' Wayne Can Say It, Why Can't I?": White Male Undergraduates Using the N-Word. (29th July 2021) - Cabrera, Nolan L.; Hill-Zuganelli, Dee
ABSTRACT: This paper critically analyzes the narratives of 62 White male undergraduates and their consistent use of the n-word during their college years. Almost all heard and/or used the n-word, but rarely did they believe using the n-word was racist. Despite these beliefs, the participants almost never used any form of the n-word in the presence of People of Color, Black people in particular. There were some who felt uncomfortable with their friends' casual use of the n-word, but they rarely challenged their peers fearing social discomfort. The analyses highlight different levels of responsibility for the racism embedded in both speaking and hearing this word as well as the White campus-based segregation that allowed the use of the term to flourish.